Relationship Between Work Attitude and Musculoskeletal Disorders in Central Weaving Industry Craftmen in Dalangan Village, Tawangsari District, Sukoharjo Regency - Arista Ririn Yulianti; Wartini Wartini; Nur Ani; Iik Sartika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Work in the informal sector, such as weaving, has high health risks due to the repetitive nature and static positions required. Weavers often experience Musculoskeletal Disorders (MSDs) due to sitting too long in front of the loom for about 8 hours. This condition causes muscle contractions in the shoulders and neck, reduces blood flow, and causes pain and fatigue. A study of two sarong weaving industries in Dalangan Village found that 70% of 10 workers complained of low back pain. Many workers work with non-ergonomic positions and inappropriate equipment. Improvements in work attitudes are needed so that workers' health and productivity are maintained. This study aims to determine the relationship between work attitudes and MSDs disorders in the central craftsmen of the weaving industry. This research is a quantitative study using observational analysis method with cross sectional approach. The population was 35 from 4 locations with a sample of 35 respondents taken using total sampling technique. Assessment for work attitudes using the Rapid Entire Body Assessment (REBA) and for Musculoskeletal Disorders (MSDs) experienced using the Nordic Body Map (NBM). The results of the Spearman correlation test showed no significant relationship between work attitudes and musculoskeletal complaints with a p-value = 0.261 (p < 0.05) and a correlation coefficient value of r = 0.195 which is included in a weak correlation with a positive direction. The study shows there is no significant relationship between work attitude and musculoskeletal disorders in weaving industry workers. Routine ergonomics education is recommended to prevent complaints and maintain sustainable occupational health.